UNVEILING PROACTIVE WORK BEHAVIOR IN MEDIATING THE EFFECT OF GRIT ON EMPLOYEE WORK EFFECTIVENESS - Wibawanti, Andjar Budi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study explores the association between proactive work behavior (PWB), which is a mediator between employee grit and work effectiveness. Sixty-three employees of the Secretariat General and Directorates within the Directorate General of Transportation of the Indonesian Ministry of Transportation provided data for this research, which was collected through a questionnaire on a Likert scale. Structural equation modeling (SEM) results demonstrated that grit enhanced PWB, which in turn significantly impacted work effectiveness both directly and indirectly. It added to the process by which work effectiveness was impacted by grit. As a result, leaders have to establish the appropriate policies to support employee grit and PWB simultaneously. Therefore, additional research needs to be done in a wider range of sectors and organizations.